Penhora de criptoativos no processo civil - Fontana, Lucca Andrea Gabrielle (2025)
This paper aims to analyze the legal challenges involved in the judicial seizure of crypto-assets under Brazilian civil procedure, with particular emphasis on cryptocurrencies. It evaluates the effectiveness of existing legal mechanisms in addressing the unique characteristics of these digital assets, such as volatility, decentralization, and the technical complexity of traceability. The research investigates both the Brazilian Judiciary’s approach in the face of regulatory gaps and the impact of recent legislative developments. Additionally, the research engages with international experiences in order to propose solutions for improving civil enforcement mechanisms in the context of emerging digital asset structures